Qualitative analysis of concordance in advance care planning discussions between patients with advanced cancer and their surrogate decision makers - Qian Chen; Mengna Liang; Jingzhang Liang; Jiefang Xu; Qiaocong Lu; Siqi Liang (BMJ Open)
Objectives This study aimed to explore the concordance in advance care planning (ACP) discussions between patients with advanced cancer and surrogate decision makers within an oncology ward.Design Purposive and snowball sampling methods were used in this qualitative study, which involved conducting semistructured interviews to gather patients with advanced cancer and their surrogate decision makers. Interpretative phenomenological analysis was performed on the interview data to identify commonalities and differences in ACP discussions and to explore the factors influencing these differences.Setting The research was conducted in the oncology ward of a tertiary hospital located in Foshan, China.Participants Participants included a total of 15 pairs of patients with advanced cancer and their surrogate decision makers in oncology wards.Results Interpretative phenomenological analysis yielded three main themes and fourteen subthemes. The identified themes were: (1) personal factor; (2) family intrinsic factors and (3) external factor.Conclusion This study revealed the consistency of ACP between patients with advanced cancer and their surrogate decision makers in China and its influencing factors. Future research should further explore family-centred ACP practices, delve into how family factors influence the implementation of ACP for patients and develop conceptual frameworks and implementation strategies for ACP that align with Chinese cultural values and healthcare systems. These efforts will contribute to enhancing understanding in clinical practice, advancing scientific research and guiding policy formulation. ACP holds promise as a crucial intervention to improve the quality of end-of-life care for patients with advanced cancer in China, playing a central role in the field of palliative care in the country.